COMMENTS ON THE VOCALIZATION OF THE SUFFIX PRONOUN OF THE THIRD FEMININE SINGULAR IN PHOENICIAN AND PUNIC - Krahmalkov, Charles R. (Journal of Semitic studies, 1972)
CHARLES R. KRAHMALKOV; COMMENTS ON THE VOCALIZATION OF THE SUFFIX PRONOUN OF THE THIRD FEMININE SINGULAR IN PHOENICIAN AND PUNIC, Journal of Semitic Studies, Vo